MARKETING AND CHALLENGES FOR THE COVID 19 VACCINE IN UTTARAKHAND - Ragaur, Sandhya (International Journal of Research -GRANTHAALAYAH, 2023)
Background: The first case in Uttarakhand was recorded on March 15, 2020, and the total positivity rating was 17.5 on May 22, 2020. Given that Vaccination was the only “foolproof” way to fight against COVID-19, the inoculation of the population was necessary to revitalize the economy, protect its citizens and take a step closer to defeating the pandemic. Thus, Vaccine Drives were heavily incentivized and marketed to the general population. Methods: In this research paper, the marketing, and challenges of vaccination in Uttarakhand have been analysed by collecting primary data through questionnaires and secondary data through research papers, articles, official government websites and newspapers Findings: The Uttarakhand government employed various strategies to vaccinate the general public. They provided non-monetary incentives, appointed vaccine ambassadors, provided for workplace vaccinations and associated with private offices to run vaccine programs. These were met with certain barriers caused mainly due to the demographic factors such as nature of locality (rural/ urban), gender, etc. and vaccination shortage. Conclusion: The programs of the Uttarakhand Government were met with mostly satisfactory responses. The problems causing barriers to vaccination have mostly straightforward answers which have to be implemented through long-term plans such as providing technical skills, better accessibility in rural regions and education to be scientifically aware among the general populace.